"COORDINATION OF COLORS IN MUSIC" (WITH SPECIAL REFERENCE TO RAGAMALA PAINTINGS): ‘‘संगीत में रंगो का समन्वय‘‘ (रागमाला चित्रों के विशेष संदर्भ में) - Mathur, Kumkum (International Journal of Research -GRANTHAALAYAH, 2014)
The third chapter in the book titled Kamsutra (2E-3E century AD) of Vatsyayan Muni discusses the forty-four arts. In which the first place is Geethan (music), in the second place Badyam (instrumental music), in the third place Nrityam (dance) and in the fourth place, Alakhya i.e. ’painting’. The commentary (11-12th century) of the third chapter of the first authority of the Kamasutra (Jayamangala) was presented by Pandit Yashodhar. Under which the six parts of Alekhya (painting) were described. 1. Variation 2. Proof, 3. Bhava, 4. Lavanya Yojana, 5. Analogy and sixth varna-breach. "Ring-break" means the combination of different colors with proper balance. In the ’conspiration’ (six parts of the painting), the color of the varna is placed at the end because it is the extreme point of ’conspiracy’ practice. We can imagine the remaining five organs, but it is necessary to do long exercises by paintbrush to break the varna. Varna jnanam sada nasti kya tasya japapujanai: that is, it is useless to practice the five limbs of ’Shadang’ without Varna Gyan. वात्सायन मुनि के कामसूत्र (2 ई-3 ई शताब्दी ई0) नामक ग्रन्थ में तीसरे अध्याय के अन्तर्गत चैसठ कलाओं का विवेचन किया गया है। जिनमें प्रथम स्थान पर गीतं (संगीत) द्वितीय स्थान पर बाद्यं (वाद्य- वादन), तृतीय स्थान पर नृत्यं (नाच) तथा चतुर्थ स्थान पर आलेख्यं अर्थात ‘चित्रकला’ को माना है। ‘कामसूत्र के प्रथम प्राधिकरण के तीसरे अध्याय की ‘जयमंगला’ नामक टीका (11-12वी शताब्दी) पण्डित यशोधर द्वारा प्रस्तुत की गई। जिसके अन्तर्गत आलेख्य (चित्रकला) के छह अंग वर्णित किये गये। 1. रूपभेद 2. प्रमाण, 3. भाव, 4. लावण्य योजना, 5. सादृश्य एवं छटवां वर्णिका-भंग। ‘‘वर्णिका-भंग’’ अर्थात विभिन्न रंगों का उचित सन्तुलन के साथ संयोजन। ’षडंग’ (चित्रकला के छह अंगों) में वर्णिका भंग का स्थान अंत में इसीलिये रखा गया क्योंकि यह ‘षडंग’ साधना का चरम बिन्दु है। शेष पांचों अंगों की हम कल्पना कर सकते हैं परन्तु वर्णिका भंग हेतु तूलिका द्वारा दीर्घ अभ्यास करना आवश्यक है। वर्ण ज्ञानं सदा नास्ति किं तस्य जपपूजनैः अर्थात वर्णज्ञान के बिना ’षडांग’ के पांच अंगों की साधना करना व्यर्थ है।1